Non-muscle-invasive bladder cancer: a vision for the future. (4th March 2017) - Malmström, Per-Uno; Agrawal, Sachin; Bläckberg, Mats; Boström, Peter J.; Malavaud, Bernard; Zaak, Dirk; Hermann, Gregers G.
Abstract: The management of non-muscle-invasive bladder cancer (NMIBC) has evolved from the first reports on bladder endoscopy and transurethral resection to the introduction of adjuvant intravesical treatment. However, disease recurrence and progression remain an ongoing risk, placing a heavy burden on healthcare resources and on patients' quality of life. Deeper understanding of the molecular basis of the disease and developments in optics, lasers and computer science are already offering opportunities to revolutionize care and improve long-term prognosis. This article discusses developments likely to cause a paradigm shift towards the delivery of personalized care and reduced burden of disease in NMIBC.